Futsal Field Management Information System based on Android in 212 Galuh Mas Karawang - Eko Pramono; Saepul Aripiyanto; April Lia Hananto (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
This futsal field booking application is used to make it easier for tenants to know the empty futsal court schedule, to provide convenience in the process of renting a futsal field schedule without having to come directly to the futsal venue. Making this application is done by the System Development Life Cycle Method. This application is implemented with the Codeigniter framework, PHP programming language, MySQL database as a data storage medium and testing methods using black box testing. As for the futsal field schedule rental uses Gammu and modem as media. This application can be used by 3 users, namely admin, provider and tenant. Admin can do provider approval. Providers can process field data, rental rates, tenants, bookings, payment confirmations, galleries and providers. Tenants can book via Mobile and see available field schedule information, activation and payment confirmation